Genetic markers associated with seed longevity and vitamin E in diverse Aus rice varieties - Lee, Jae-Sung; Kwak, Jieun; Hay, Fiona R. (Cambridge University Press, 2020)
Vitamin E is known to scavenge lipid peroxy radicals and has a purported role in preventing seed deterioration during storage. In our previous studies using 20 rice varieties from different variety groups, the specific ratio of vitamin E homologues rather than total vitamin E content was associated with seed longevity. To validate this result, we extended the experiment to a rice panel composed of 185 Aus (semi-wild rice) varieties. Seed longevity values were determined through storage experiments at 45°C and 10.9% seed moisture content (MC). Eight types of vitamin E homologues (α-, β-, γ- and δ-tocopherol/tocotrienol) were quantified by ultra-performance liquid chromatography. The theoretical initial viability in NED, Ki, was positively correlated with γ- and δ-tocopherols and negatively correlated with α-tocotrienol. The time for viability to fall to 50% during storage at elevated temperature and relative humidity, p50, was positively correlated with δ-tocopherol. The harvest MC was negatively correlated with all seed longevity traits. Taking this factor into account in a genome-wide association (GWA) analysis, we were able to correct false positives. A consistent major peak on chromosome 4 associated with −σ−1 was detected with a mixed linear analysis. Based on rice genome annotation and gene network ontology databases, we suggest that RNA modification, oxidation–reduction, protein–protein interactions and abscisic acid signal transduction play roles in seed longevity extension of Aus rice. Although major GWA regions were not overlapped across traits, three genetic markers, on chromosomes 1, 3 and 4, were associated with both δ-tocopherol and Ki and two markers on chromosome 1 and 8 were associated with both δ-tocopherol and p50.